Un gazetier des places portuaires françaises du xviiie siècle - Christine Plumejeaud-Perreau; Mélissa Mimouni; Alain Bouju; Christian Pfister-Langanay; Thierry Sauzeau; Silvia Marzagalli (Humanités Numériques)
This article presents the methodology and choices we made to produce and publish on the semantic Web a gazetteer of French ports in activity between 1749 and 1815 and of foreign ports they were connected to, including their belonging to historical maritime and fiscal administrative districts, and to political entities. The paper focuses in particular on how we dealt with imperfect data: the sources we used are lacunary and existing open data induce some uncertainties because they are not specifically devoted to maritime history. This work is part of the ANR program PORTIC (2019-2023), which studies shipping activities and trade in France in the second half of the eighteenth century, with an emphasis on the visualisation of imperfect data.